ANALYSIS OF THE RELATIONSHIP BETWEEN EDUCATION AND LEVEL OF ORAL HEALTH KNOWLEDGE IN POSYANDU CADRES - Theresia, Tiarma Talenta; Cikagri, Alifia Adinda; Astoeti, Tri Erri; Goalbertus (Universitas Airlangga, 2024)
Introduction: The prevalence of dental caries in West Jakarta was 44.24%, and one of the prevention efforts that could be taken was health promotion. Posyandu cadres are health volunteers selected from the community who voluntarily contribute to improving community health. Posyandu cadres are important as oral health educators in the community; as extension workers, Posyandu cadres must have the necessary knowledge, skills, and experience to be trusted as a source of information; one of the factors that influence participation is knowledge. Aims: This research examines the relationship between education and oral health knowledge among Posyandu Cadres in Kemanggisan District. Method: Analytical observational research was conducted using a cross-sectional design method involving 73 Posyandu cadres. The research was conducted by taking data from the results of questionnaires filled in directly from August – September 2023. Result: Of the 73 respondents, 41.1% had high knowledge, and 58.9% had low knowledge. Subjects who had a high level of education had higher odds of having good knowledge (adjusted OR: 147.93; 95% CI: 3.52 - 6218.85, P = 0.009). Conclusion: The higher the cadre's education, the better their oral health knowledge will be.